2010
DOI: 10.3390/md8030763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Marine Polycyclic Polyethers via Endo-Selective Epoxide-Opening Cascades

Abstract: The proposed biosynthetic pathways to ladder polyethers of polyketide origin and oxasqualenoids of terpenoid origin share a dramatic epoxide-opening cascade as a key step. Polycyclic structures generated in these biosynthetic pathways display biological effects ranging from potentially therapeutic properties to extreme lethality. Much of the structural complexity of ladder polyether and oxasqualenoid natural products can be traced to these hypothesized cascades. In this review we summarize how such epoxide-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 165 publications
0
43
0
Order By: Relevance
“…A related bis-ether structure is also thought to be an intermediate before the formation of bridged ketal structure in pectenotoxins produced by dinoflagellates (Van Wagoner et al, 2014). The ether ring-formation of two tetrahydrofuran rings in 1 occurs tentatively via 5-exo-tet reaction instead of 6-endo-tet ringformation, which is favoured in the formation of ladder polyether toxins such as brevetoxins and yessotoxins (Vilotijevic and Jamison, 2010). A possible mechanism for formation of 1 is presented in Fig.…”
Section: Biosynthesismentioning
confidence: 99%
“…A related bis-ether structure is also thought to be an intermediate before the formation of bridged ketal structure in pectenotoxins produced by dinoflagellates (Van Wagoner et al, 2014). The ether ring-formation of two tetrahydrofuran rings in 1 occurs tentatively via 5-exo-tet reaction instead of 6-endo-tet ringformation, which is favoured in the formation of ladder polyether toxins such as brevetoxins and yessotoxins (Vilotijevic and Jamison, 2010). A possible mechanism for formation of 1 is presented in Fig.…”
Section: Biosynthesismentioning
confidence: 99%
“…Tetrahydrofuran ring was formed by Baldwin's rules of molecular open-loop and close-loop response by 5-exo-tet cyclization [20], [21], [22], [23].…”
Section: Semisynthesis Of 20(s)-ocotillol-type Saponinsmentioning
confidence: 99%
“…Much effort has been directed at overturning the kinetic preference in single epoxide-opening events, and subsequently toward extending iterative methods to the more complex polyepoxide cascade openings 41 . With a focus on methods for the assembly of fused tetrahydropyrans (THPs), many have found that inclusion of alkenyl, alkynyl, alkyl or silyl groups pendant to the cleaved epoxides is required to stabilize the partial positive charge that develops in the endo transition state [42][43][44][45][46] .…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 99%